Método eletroanalítico alternativo para análise de HPA’s (acenafteno e naftaleno) em água subterrânea de posto de combustível - FERREIRA, Ana Paula Mota (2021)
Groundwater is an important source of drinking water and does not require pre-treatment, as the filtration and purification processes of the subsoil promote water purification. Although more protected, groundwater is not safe from pollution, and among the major polluting sources we have the oil industries, which are responsible for serious accidents involving oil products. A major current concern is gas stations. At resale or distributor stations, all fuels are stored in underground tanks and not replacing these storage tanks is one of the main reasons that lead to groundwater contamination. Due to the increase in areas impacted by hydrocarbons resulting from the spillage of fuels in the soil, there is a need to quantify these contaminants in groundwater samples, given the importance it has as a drinking water reserve. This work proposes a method for the determination of the Acenaphthene (ACE) and Naphthalene (NAF) polyaromatic hydrocarbons (HPAs) in aqueous medium with a cobalt phthalocyanine modified glassy carbon electrode (ECV / CoPc), using Square Wave Voltammetry techniques (VOQ) and Differential Pulse Voltammetry (VPD). Experimental parameters were optimized for the purpose of determination of ACE and NAF in groundwater collected in gas stations wells, São Luís-MA. After study to obtain the optimum conditions for the VOQ and VPD techniques, the ACE and NAF were determined in a 0.2 mol L-1 Britton-Robinson (BR) buffer solution at pH 2.0 as a support electrolyte. ACE and NAF oxidation occurred at 1.0 and 1.3V (vs Ag/AgCl), respectively. Good results were obtained for ACE in terms of detection limit (2,85 x 10-9 mol L -1 ), precision (3% of CV) and accuracy (99.9% of recovery), while for NAF the detection limit was 3,01 x 10-9 mol L-1 , CV was 4.8% (accuracy) and recovery was 100.5% (accuracy). These results indicate that the proposed procedure is a good alternative for the analysis of ACE and NAF in groundwater of gas stations.